2009
DOI: 10.1002/jst.89
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis in freestyle snowboarding: application of a full-body inertial measurement system and a bilateral insole measurement system

Abstract: Several investigations show that 5-28% of all snowboarding injuries relate to the ankle joint complex. To reduce the risk of ankle injuries, the development of enhanced snowboard equipment is considered. Therefore, it is essential to understand the biomechanics in snowboarding. Scientific studies investigating the ankle joint complex in freestyle snowboarding, including inrun, flight phase, and landing, are so far not available. An auspicious method to determine relevant kinematical and kinetic parameters is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Wouda et al (2018) also reported strong agreement (r > 0.98) between Xsens and 3DOMA at the hip and knee during treadmill running at different speeds, however when compared with our study, larger errors were observed (mean difference <18.1° at the hip and <10.2° at knee). Krüger and Edelmann-Nusser (2009) also reported strong agreement (r = 0.77-0.96) and errors of less than 5° for knee angles during a snowboarding turn, when compared with video analysis. When compared with the present study, smaller measurement error has been shown at the knee (peak flexion: 0.8°, peak extension: 1.4° and mean angular velocity: 14°.s −1 ) and hip (hip extension: 0.5°) during a kicking action (Blair et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…Wouda et al (2018) also reported strong agreement (r > 0.98) between Xsens and 3DOMA at the hip and knee during treadmill running at different speeds, however when compared with our study, larger errors were observed (mean difference <18.1° at the hip and <10.2° at knee). Krüger and Edelmann-Nusser (2009) also reported strong agreement (r = 0.77-0.96) and errors of less than 5° for knee angles during a snowboarding turn, when compared with video analysis. When compared with the present study, smaller measurement error has been shown at the knee (peak flexion: 0.8°, peak extension: 1.4° and mean angular velocity: 14°.s −1 ) and hip (hip extension: 0.5°) during a kicking action (Blair et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…Internationally, the implementation of this technology in science and sport science, has a wide application in some studies and researches, based on the use of complete systems such as Moven © , Animazoo © or the use of components of inertial navigation systems (Willemsen et al, 1990;Davey et al, 2005;Welk, 2005;Kavanagh et al, 2006;Bamberg et al, 2008;Tilmann et al, 2008;Hesami et al, 2008;Kruger and Edelmann-Nusser, 2009;Meamarbashi, 2009;Mbaitiga, 2009).…”
Section: Introductionmentioning
confidence: 99%